Evaluating the Properties of a Frailty Index and Its Association With Mortality Risk Among Patients With Systemic Lupus Erythematosus. Issue 8 (29th May 2019) - Legge, Alexandra; Kirkland, Susan; Rockwood, Kenneth; Andreou, Pantelis; Bae, Sang‐Cheol; Gordon, Caroline; Romero‐Diaz, Juanita; Sanchez‐Guerrero, Jorge; Wallace, Daniel J.; Bernatsky, Sasha; Clarke, Ann E.; Merrill, Joan T.; et al.
Abstract : Objective: To evaluate the properties of a frailty index (FI), constructed using data from the Systemic Lupus International Collaborating Clinics (SLICC) inception cohort, as a novel health measure in systemic lupus erythematosus (SLE). Methods: For this secondary analysis, the baseline visit was defined as the first study visit at which both organ damage (SLICC/American College of Rheumatology Damage Index [SDI]) and health‐related quality of life (Short‐Form 36 [SF‐36] scores) were assessed. The SLICC‐FI was constructed using baseline data. The SLICC‐FI comprises 48 health deficits, including items related to organ damage, disease activity, comorbidities, and functional status. Content, construct, and criterion validity of the SLICC‐FI were assessed. Multivariable Cox regression was used to estimate the association between baseline SLICC‐FI values and mortality risk, adjusting for demographic and clinical factors. Results: In the baseline data set of 1, 683 patients with SLE, 89% were female, the mean ± SD age was 35.7 ± 13.4 years, and the mean ± SD disease duration was 18.8 ± 15.7 months. At baseline, the mean ± SD SLICC‐FI score was 0.17 ± 0.08 (range 0–0.51). Baseline SLICC‐FI values exhibited the expected measurement properties and were weakly correlated with baseline SDI scores (r = 0.26, P < 0.0001). Higher baseline SLICC‐FI values (per 0.05 increment) were associated with increased mortality risk (hazard ratio 1.59, 95% confidence interval 1.35–1.87), after adjusting for age, sex, steroid use, ethnicity/region, and baseline SDI scores. Conclusion: The SLICC‐FI demonstrates internal validity as a health measure in SLE and might be used to predict future mortality risk. The SLICC‐FI is potentially valuable for quantifying vulnerability among patients with SLE, and adds to existing prognostic scores.